2011
DOI: 10.3136/fstr.17.499
|View full text |Cite
|
Sign up to set email alerts
|

Immunoblotting Analysis of nsLTP1 in Cereal Grains with Antiserum Raised against Recombinant Rice nsLTP1

Abstract: Nonspecific lipid transfer protein 1 (nsLTP1) is widely distributed in plants and has been recognized as a widely cross-reacting plant pan-allergen. In the present study, a recombinant protein of rice nsLTP1 was prepared with an Escherichia coli expression system, and polyclonal antiserum was raised by immunizing rabbits with this recombinant nsLTP1. The antiserum specifically immunoreacted with rice nsLTP1 and homologous nsLTP1 proteins of other kinds of cereal grains. Moreover, the antiserum was applied to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…3-2, lanes G-I; open arrowhead). Lang reported that variation in the migration speed of LTP1 was observed among rice, millet, rye, and barley (Lang et al, 2011). Differences in migration speed between barley and rice LTP1 is consistent with Lang's report, which used a rabbit polyclonal antibody against recombinant rice LTP1 (Lang et al, 2011).…”
Section: Localization Of Barely β-Amylase During Cooking Of Rice Mixesupporting
confidence: 84%
“…3-2, lanes G-I; open arrowhead). Lang reported that variation in the migration speed of LTP1 was observed among rice, millet, rye, and barley (Lang et al, 2011). Differences in migration speed between barley and rice LTP1 is consistent with Lang's report, which used a rabbit polyclonal antibody against recombinant rice LTP1 (Lang et al, 2011).…”
Section: Localization Of Barely β-Amylase During Cooking Of Rice Mixesupporting
confidence: 84%
“…The rabbit antisera were prepared by immunizing rabbits with the respective recombinant proteins as previously described. 28,32) Immunoblotting and signal detection were also carried out as previously described. 28) The chemiluminescent signal was detected by the Pharos FX molecular imager system (Bio-Rad Laboratories), the signal intensity being quantified by using Quantity One 1-D Analysis software (Bio-Rad Laboratories).…”
Section: Methodsmentioning
confidence: 99%